Pengaruh Teknologi Informasi terhadap Peningkatan Kualitas Pelayanan Publik melalui Kinerja Tenaga Pelayanan Kesehatan : (Studi pada Tenaga Pelayanan Kesehatan UPT. Puskesmas Pegantenan Kabupaten Pamekasan) - Sujiah Rahayu Ningsih; Hadi Susanto; Abdul Fatah Fanani (Trending: Jurnal Manajemen dan Ekonomi, 2025)
Sujiah Rahayu Ningsih, 2025. The Influence of Information Technology on Improving the Quality of Public Services Through the Performance of Health Care Workers (A Study of Health Care Workers at the Pegantenan Community Health Center in Pamekasan Regency, Wijaya Putra University Graduate Program). The type of research is cross-sectional because within a specific time frame/simultaneously, the researcher conducted observations and recorded the responses provided by the respondents using a quantitative approach. The research sample consisted of 54 respondents. Data analysis was conducted using SEM-PLS. The objectives of the research include: 1) To test and analyze whether information technology has an impact on the quality of public services. 2) To test and analyze the influence of information technology on the performance of healthcare workers. 3) To test and analyze the influence of healthcare workers’ performance on public service quality. 4) To test and analyze the indirect influence of information technology on public service quality through healthcare workers’ performance. The research results indicate that: 1) Information technology significantly influences the improvement of public service quality. 2) Information technology has a significant impact on the performance of healthcare workers. 3) The performance of healthcare workers has a significant impact on improving service quality. 4) Information technology has an indirect and significant impact on improving service quality, mediated by the performance of healthcare workers.